Nanotechnology for energy harvesting: from fundamental triboelectrification to self-powered smart applications via triboelectric and piezoelectric nanogenerators - Silva, Rafael Resende Assis (Universidade Federal de São Carlos, 2025)
The urgent global demand for sustainable, decentralized, and reliable energy solutions has fuelled research into nanotechnology-based energy harvesting. This thesis advances both the fundamental understanding of triboelectrification and the development of multifunctional nanogenerators - triboelectric (TENGs) and piezoelectric (PENGs) - with the objective of enabling next-generation self-powered smart applications. To establish the foundation, a comprehensive analysis of the triboelectric effect - particularly under dirt-prone environments - was conducted alongside the role of functional materials for environmental energy harvesting and smart sensing. Charge-transport mechanisms, device architectures, and stimuli-responsive systems were examined, highlighting durability, contamination, and variability challenges, and providing the conceptual framework for smart TENGs applications developed in this thesis. Systematic investigations of liquid-solid triboelectrification revealed how flow dynamics, device structure, and ionic content govern electrical output. To translate TENGs into self-powered pressure sensors, a hierarchical surface-engineering strategy enhanced output and introduced self-cleaning capability for durable e-skin. Dual-scale micro/nanostructuring with chemical modification produced superhydrophobic surfaces, achieving superior energy harvesting (~270 mW·m-2), high-pressure sensitivity, and 94% contaminant removal. Toward sustainable electronics, laser-induced graphene (LIG) electrodes were developed for food-quality monitoring and integrated with self-powered barcodes via TENGs. Anthocyanin incorporation catalyzed graphene synthesis (ID/IG = 0.87) and conferred NH3 responsiveness, enabling tri-modal detection-colorimetric, electrochemical, and RFID-with a 110-ppm detection limit and 1.2 Ω·m3·mg-1 sensitivity, thereby allowing real-time, wireless, and reagent-free freshness monitoring. In the biomedical domain, PENGs and mechanically triggered electric fields developed stimuli-responsive gyroid scaffolds with NaNbO3 nanostructures for bone regeneration. Combining hierarchical porosity with ultrasound stimulation, these scaffolds enhanced cell proliferation, alignment, and mineralization, achieving >1200% calcium deposition and establishing bioelectric scaffolds as transformative for regenerative therapies. Collectively, this thesis demonstrates how multifunctional nanogenerators, grounded in fundamental mechanisms, can be engineered as a sustainable and versatile nexus for self-powered sensors in healthcare, agriculture, smart packaging, and pressure-sensing applications.
Nanotecnologia para aproveitamento de energia: da triboeletrificação fundamental às aplicações inteligentes autoalimentadas por nanogeradores triboelétricos e piezoelétricos
Keywords: Nanotecnologia; Nanotechnology; Nanogeradores triboelétricos (TENGs); Triboelectric nanogenerators (TENGs); Geração de energia; Sensores inteligentes; Smart sensors; Polímeros; Polymers; Sensores autoalimentados; Self-powered sensors; Grafeno induzido a laser; Laser-induced graphene; Engenharia de superfície; Surface engineering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 3. Saúde e Bem-Estar; 4. Educação de Qualidade; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima